2017
DOI: 10.14814/phy2.13466
|View full text |Cite
|
Sign up to set email alerts
|

Moderate exercise training does not prevent the reduction in myocardial L-type Ca2+ channels protein expression at obese rats

Abstract: Authors have showed that obesity implicates cardiac dysfunction associated with myocardial L‐type calcium channels (LTCCs) activity impairments, as well as moderate exercise training (MET) seems to be an important therapeutic tool. We tested the hypothesis that MET promotes improvements on LTCCS activity and protein expression at obesity induced by unsaturated high‐fat diets, which could represent a protective effects against development of cardiovascular damage. Male Wistar rats were randomized in control (C,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 63 publications
(229 reference statements)
0
10
0
Order By: Relevance
“…The weekly monitoring of body weight aimed to identify the moment of significant increase in this parameter in animals under the influence of treatments with hypercaloric diets in relation to those treated with a standard diet to effectively evidence the duration of obesity from a given experimental model [ 26 , 27 ]. In this context, the HF diet promoted a significant increase in body weight in relation to the animals fed a control diet (C) from the seventh week until the end of treatment (20th week).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The weekly monitoring of body weight aimed to identify the moment of significant increase in this parameter in animals under the influence of treatments with hypercaloric diets in relation to those treated with a standard diet to effectively evidence the duration of obesity from a given experimental model [ 26 , 27 ]. In this context, the HF diet promoted a significant increase in body weight in relation to the animals fed a control diet (C) from the seventh week until the end of treatment (20th week).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in agreement with the literature, in which it is evidenced that the body weight gain occurs gradually during the feeding period with an excess of fat [ 28 , 29 ]. One important aspect is that although it is possible to note or evidence the difference in body weight after two weeks of the experimental protocol, the obesity phenotype becomes more apparent after prolonged periods, generally after four weeks [ 11 , 26 , 30 ]. Corroborating this information, the HFHS showed an elevation in body weight only in the last 4 weeks of the experimental protocol.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, RT was not able to modulate the body weight in ObRT in comparison with Ob group from 17 th to 2 6th weeks. These findings are in disagreement with the studies found in the literature, indicating that RT was a viable non-pharmacological strategy to reduce body weight [26,31,44]. On the other hand, with regard to the effect of RT associated with the high-fat diet, it was possible to verify the effectiveness of this type of training to reduce epididymal (40.5%) and visceral (37%) fat pads, but without changes in total adiposity.…”
Section: Discussionmentioning
confidence: 61%
“…16 Other investigations have reported impaired cardiac contraction, showed by in vitro papillary muscles analysis of obese rats in experimental models with15 weeks of diet. 7,17,18 There are also reports of unchanged cardiac function after 20, 9 30, 19 and 32 14 weeks of dietary intervention. Therefore, cardiac performance should be further studied in high-fat diet-induced obesity experiments.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 These responses include disorders in expression and functioning of peptides involved with intracellular calcium handling during muscle contraction and relaxation. 7,[12][13][14] However, there are important divergences among studies regarding potential effects of high-fat diet induced obesity on myocardial performance. Jacobsen et al 15 found increased contractile phase during inotropic maneuver of papillary muscle in obese rats after three weeks of diet; other authors have found higher myocardial shortening velocity in experiments of 20, 8 30, 11 33, 13 and 35 weeks.…”
Section: Introductionmentioning
confidence: 99%